Influence of Nd:YAG laser on the penetration of a bioceramic root canal sealer into dentinal tubules: A confocal analysis - Jardim Del Monaco, Rodrigo; Tavares de Oliveira, Marcelo; Lima, Adriano Fonseca de; Scarparo Navarro, Ricardo; Zanetti, Raquel Virgínia; de Fátima Teixeira da Silva, Daniela; Horliana, Anna Carolina Ratto Tempestini (PLOS ONE, 2018)
Objective The aim of this in vitro study, is to evaluate the penetration of a bioceramic root canal sealer into dentinal tubules at 3 mm and 5 mm from the apex after Nd:YAG laser irradiation. Methods Forty freshly extracted human mandibular premolars were prepared using Reciproc® and irrigated with 17% ethylenediaminetetraacetic acid (EDTA). Teeth were divided into 4 groups: group 1, obturated with control sealer (AH Plus®); group 2, obturated with bioceramic sealer (Endosequence BC Sealer®); group 3, Nd:YAG laser + control sealer (AH Plus®); and group 4, Nd:YAG laser + bioceramic sealer (Endosequence BC Sealer®). The samples were transversely sectioned 3 mm and 5 mm from the apex and examined using confocal laser scanning microscopy. Two parameters were measured: 1) sealer penetration into dentinal tubules of the root canal and 2) sealer penetration into the perimeter of the root canal walls. Results Penetration analysis showed that bioceramic sealer had a higher penetration at depths of 3 and 5 mm than that of the control sealer, regardless of laser use (p <0.05). Perimeter analysis showed that there was no difference between both sealers at a depth of 3 mm (p <0.05), regardless of laser use. At a depth of 5 mm, bioceramic sealer and laser showed a greater perimeter of penetration (p <0.05) than the control sealer. Conclusion The use of Nd:YAG laser did not compromise the penetration of bioceramic sealer into dentinal tubules of root canals at 3 mm and 5 mm from the apex.